Heart rate and blood pressure interactions in the development of erectile dysfunction in high-risk cardiovascular patients. (29th August 2020) - Kratz, Mario T; Schumacher, Helmut; Sliwa, Karen; Schmieder, Roland; Pöss, Janine; Mahfoud, Felix; Unger, Thomas; Lonn, Eva; Koon, Teo; Mancia, Guiseppe; Sleight, Peter; Yusuf, Salim; et al.
Abstract: Aims: Erectile dysfunction (ED) is associated with cardiovascular risk factors as elevated systolic blood pressure (SBP), resting high heart rate (HR), and endothelial dysfunction and predicts cardiovascular events. However, the interaction between high HR and SBP and the development of ED remains unclear. Methods and Results: We evaluated 1015 male patients enrolled in the ED substudy of ONTARGET and TRANSCEND, examining the influence of mean HR and mean SBP obtained over all study visits (mean 10.9±1.4 study visits) and their interaction with ED. In patients without pre-existing ED, new onset ED was detected in 29% of patients below, and 41% of patients above, the median of mean HR (OR 1.72, 95% CI 1.8–2.5, p = 0.0047). In patients with pre-existing ED, high HR had no add-on effect. With or without pre-existing ED, high SBP had no influence after adjustment for covariates (OR 1.03, 95% CI 0.66–1.59, p = 0.91). In a continuous model, it was shown that effects of high HR were prominent at low Kölner (Cologne) Evaluation of Erectile Function (KEED) score baseline values and in the presence of SBP above the median. Conclusions: In patients at risk for cardiovascular events, high HR is associated with ED, whereas the effect of high SBP was not significant. High resting HR might represent a cardiovascular risk indicator. Whether HR represents a potential treatment target to improve ED in high-risk individuals must be scrutinized in prospective trials.